2006
DOI: 10.1074/jbc.m512215200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Topology of the Yeast Endoplasmic Reticulum-localized Ubiquitin Ligase Doa10 and Comparison with Its Human Ortholog TEB4 (MARCH-VI)

Abstract: Quality control machinery in the endoplasmic reticulum (ER) helps ensure that only properly folded and assembled proteins accumulate in the ER or continue along the secretory pathway. Aberrant proteins are retrotranslocated to the cytosol and degraded by the proteasome, a process called ER-associated degradation. Doa10, a transmembrane protein of the ER/nuclear envelope, is one of the primary ubiquitin ligases (E3s) participating in ER-associated degradation in Saccharomyces cerevisiae. Here we report the memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
125
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 34 publications
4
125
0
Order By: Relevance
“…The previously proposed function of the ER membrane-embedded ligases Hrd1/Der3 and Doa10 as possible channel components for substrate retrotranslocation (9,16,46) cannot hold true for Ubr1-triggered ERAD of the tested substrates in the absence of the canonical ligases. The mechanism underlying the retrotranslocation of proteins from the ER to the cytoplasm in the absence of the canonical ligases using the Ubr1-dependent ERAD route will be a challenging goal in the future.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The previously proposed function of the ER membrane-embedded ligases Hrd1/Der3 and Doa10 as possible channel components for substrate retrotranslocation (9,16,46) cannot hold true for Ubr1-triggered ERAD of the tested substrates in the absence of the canonical ligases. The mechanism underlying the retrotranslocation of proteins from the ER to the cytoplasm in the absence of the canonical ligases using the Ubr1-dependent ERAD route will be a challenging goal in the future.…”
Section: Discussionmentioning
confidence: 94%
“…It has been known for years that two polytopic ligases located in the ER membrane, Hrd1/Der3 (HMG-CoA reductase degradation/degradation of the ER) and Doa10 (degradation of alpha), play a central role in ERAD in yeast, by directing ERAD substrates to proteasomal degradation (11)(12)(13)(14)(15)(16). Previous studies on a variety of ERAD substrates revealed that, in most cases, the absence of one of the two canonical ER ubiquitin ligases does not lead to a complete block of degradation of the tested substrate.…”
mentioning
confidence: 99%
“…It was recently shown that a notable exception to this paradigm is the yeast E3 ubiquitin ligase, Doa10p. Doa10p was long known to reside in the ER membrane (Swanson et al, 2001;Kreft et al, 2006). However, recent data indicate that Doa10p exhibits dual steady-state localizations, residing and functioning in both the ER membrane where it mediates ER-associated degradation of membrane and secretory proteins, and in the INM where it mediates degradation of the nuclear transcription factor MAT␣2 (Deng and Hochstrasser, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The 1319-residue Doa10 E3 ligase has 14 transmembrane segments, a topology that appears to be conserved in the mammalian ortholog MARCH6 (TEB4) (11). Both the N and C termini of Doa10/MARCH6 are exposed to the cytosol with ubiquitin ligase activity derived from an N-terminal RING-CH domain, a subclass of RING domains (12).…”
mentioning
confidence: 99%